Elaborasi Reformasi Akuntansi Sektor Publik : Telaah Kritis terhadap Upaya Aktualisasi Kebutuhan Sistem Akuntansi Keuangan Pemerintah Daerah - Mardiasmo Mardiasmo (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2002)
Good governance and public sector accounting have a great correlation, where public sector accounting acts as a tool to elaborate good governance to a more realistic level. The elaboration in question can be achieved through management accounting, financial accounting, and public sector audit.At the moment, the applied local government autonomy and fiscal decentralisation give local government the opportunity to freely develop its local government financial management system. One way is to build a new local government financial accounting system. Because of this, a renewal in the old guidelines (Manual Administrasi Keuangan Daerah) is needed, since there are parts of it that is not in conjunction with the new law, especially those in line with the structure and process of budget, recording system, and local government financial report. Therefore, a local government financial accounting system with a new paradigm that enables the application of budgetary accounting shifts from single entry to double entry, and more comprehensive local government financial report can be achieved. Thus, the renewal will enhance local government’s accountability. Keywords: core business, performance measurement, good governance, financial report, local government financial accounting system and accountability.